Wind loading on ridge, hip and perimeter roof tiles: A full-scale experimental study. Issue 166 (July 2017) - Habte, Filmon; Asghari Mooneghi, Maryam; Baheru, Thomas; Zisis, Ioannis; Gan Chowdhury, Arindam; Masters, Forrest; Irwin, Peter
Abstract: Full-scale experiments were conducted to investigate wind loading on roof tiles in hip, ridge, and perimeter locations, identified from past storms as main points of damage initiation. The objectives were to: (i) provide test-based data on wind-induced loads for tiles, and (ii) evaluate characteristics of near-surface flows to assess tile loading models. The experiments included pressure measurements on the external surface and in the cavity underneath the tiles, and wind speed measurements near tile surfaces. The highest net uplift pressure (computed as external pressure minus the cavity pressure) was observed on the gable end ridge tiles. Except for a few non-critical cases, due to effects of pressure equalization net uplift was lower than external surface uplift. Mean wind speeds at tile surfaces were recorded that were up to 55% higher than the mean wind speed at mid-roof height in the approach flow. Two alternative models that use wind speeds near the tile surface to determine net design wind loads on tiles were investigated. The results showed that the models can underestimate wind loading. However, when used with appropriate parameters, the models can produce results comparable to those obtained using ASCE's external pressure coefficients in conjunction with pressure adjustment factors. Highlights: Experimental data of net-uplift pressure and pressure adjustment factors r on tiles. Effect of cavity pressure on net uplift depends on tile location and wind direction. Current models can underestimate loading in the ridge, hip and perimeter regions. ASCE's external pressure coefficients used with r factors can give realistic uplift.